Beyond the sophomoric promises of artificial intelligence in medicine: Artificial intelligence and medicine - Saqr, Mohammed (International Journal of Health Sciences, 2018)
AI is far from disrupting the status quo of healthcare as it currently stands, and the prospects of future advancements are unclear. The initial signs are unsatisfactory to those dreaming of robotic healthcare services, nonetheless promising to those who want to build tools that will make diagnosis easier, simpler, and faster.